Secretion of miraculin through the function of a signal peptide conserved in the Kunitz‐type soybean trypsin inhibitor family. Issue 12 (7th May 2013) - Takai, Ayako; Satoh, Makiko; Matsuyama, Tomomi; Ito, Akane; Nakata, Rieko; Aoyama, Takashi; Inoue, Hiroyasu
Abstract : Miraculin, a glycoprotein that modifies sour tastes into sweet ones, belongs to the Kunitz‐type soybean trypsin inhibitor (STI) family. To clarify the functional relation of miraculin with Kunitz‐type STIs, we investigated its subcellular localization and trypsin inhibitory activity. In transgenic Arabidopsis thaliana, miraculin, fused to yellow fluorescent protein, localized to and outside the plasma membrane depending on the putative secretion signal peptide. When transgenic seedlings were cultured in liquid medium, miraculin was present in the supernatant only after cellulase treatment. No trypsin inhibitory activity was detected in native or recombinant miraculin. In conclusion, miraculin is secreted outside the plasma membrane through the function of a signal peptide, conserved in Kunitz‐type STIs, whereas its trypsin inhibitory activity may be lost during its evolution. Abstract : A taste‐modifier protein named miraculin is secreted outside the plasma membrane. This secretion is dependent on a signal peptide conserved in Kunitz‐type STIs. Transgenic seedlings of miraculin were cultured in liquid medium. Miraculin was present in the supernatant after cellulase treatment. Miraculin may have lost trypsin inhibitory activity during its evolution.